Introduction: The Challenging Global Cancer Pandemic - Andrea Vicini (Journal of Moral Theology, 2022)
To introduce the volume, Andrea Vicini, SJ, stresses the need to address the global cancer pandemic, while the world struggles with the ongoing pandemic caused by COVID-19. Cancer affects millions of people. It is the first or second cause of death in 134 countries, the leading cause of death in most high-income countries (i.e., 10 million deaths in 2020), and the leading cause of death by disease in American children. Cancer is also unjust. Striking inequities can be traced within and between countries in cancer incidence and survival by race, ethnicity, and socio-economic-status. Survival is much higher among the wealthy than among the poor. An overview of the volume introduces the following chapters.